Mekanisme Pasar dala Konteks Islam - Sarwo Edi; Julfan Saputra; Asmaul Husna (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This paper is a literature review that aims to determine the market mechanism in the context of Islam. The methodology used is a review of studies and books both on a local Indonesian scale and on an international scale. In contrast to conventional systems, the concept of Islamic Economics emphasizes that market mechanisms and price fixing need to be regulated to achieve market equilibrium and economic justice by considering the urgency of the parties involved in the market. Fair and fair prices are prices obtained based on the power of supply (supply) and demand (demand). In the event of unfair actions that result in market distortions or prices are not at their equilibrium point, the government plays a very important role in taking regulations in the form of price fixing by looking at the factors that cause these distortions and returning prices to the original equilibrium point.